A Stage 1 Pilot Cohort Exploring the Use of EMDR Therapy as a Videoconference Psychotherapy During COVID-19 With Frontline Mental Health Workers: A Proof of Concept Study Utilising a Virtual Blind 2 Therapist Protocol - Farrell, Derek; Fadeeva, Anastasia; Zat, Zeynep; Knibbs, Lorraine; Miller, Paul; Barron, Ian; Matthess, Helga; Matthess, Cordula; Gazit, Neta; Kiernan, Matthew D. (Frontiers in Psychology, 2022)
Objective The Covid-19 pandemic has had a major impact in the delivery of psychological treatment. Due to social distancing requirements provision moved to video-conferencing psychotherapy (VCP). There is a paucity of empirical data supporting the efficacy of EMDR therapy as a VCP. This stage 1 pilot study tested an EMDR therapy scripted protocol – Virtual Blind 2 Therapist (VB2T) on frontline mental health workers as a VCP regarding fitness for purpose, distinctiveness, relevance, and efficiency. Methods Twenty-four participants were recruited to the study. The design included a one-session treatment intervention obtaining measures pre, post, one-month, and six-month follow-up. This treatment session used a ‘Blind 2 Therapist’ EMDR therapy scripted protocol as video-conference psychotherapy that involves non-disclosure of traumatic memory. The research explored the treatment effect on the core characteristics of the trauma memory including subjective disturbance, belief systems, memory intensity, vividness, and levels of emotionality. Additionally, the research explored participants’ experiences of adverse and benevolent childhood experiences (ACEs/BCEs) during their childhood. Results Regarding the four tests - fitness for purpose, distinctiveness, relevance, and efficiency results are favourably suggesting potential clinical benefits of using EMDR as video-conference psychotherapy. That said this is a proof-of-concept study showing positive results, however, no clinical population or control group was used. The purpose of the study is to explore the potential for scalability towards a larger clinical trial. The treatment intervention was achieved irrespective of either adverse or benevolent childhood experiences (ACEs/BCEs) during childhood Conclusion The research tentatively supports the case for EMDR therapy as a credible treatment when used as a video conference psychotherapy, and in using the Blind 2 Therapist protocol. However, more research is needed to scale towards a clinical trial.